Not anointing, but justice? A critical reflection on the anointing of Pentecostal prophets in a context of economic injustice - Banda, Collium (Verbum et ecclesia, 2018)
To what extent does the anointing of the Pentecostal prophets provide a meaningful way of responding to poverty in an unjust economic context? Using Zimbabwe as a case study, this article critically evaluates the growing reliance on the anointing of the Pentecostal prophets by many poor people as a way of responding to their economic poverty. The practice is considered to provide miraculous power to pave the way for a desired economic outcome. The article highlights that many people turn to the anointing of Pentecostal prophets as a form of spiritualised activism against unjust economic forces in the country. The article proposes that rather than anointing, seeking justice should be the adopted means of responding to unjust economic systems. It examines aspects that should inform the church's quest for economic justice.Intradisciplinary and/or interdisciplinary implications: This study relates to the disciplines of systematic theology, public theology and sociology of religion by calling on Christians to allow other disciplines to inform their desire to eradicate poverty.